2003
DOI: 10.1095/biolreprod.103.016147
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Phenotypic and Epigenetic Variation in Cloned Swine1

Abstract: Cloning by somatic cell nuclear transfer can result in the birth of animals with phenotypic and gene expression abnormalities. We compared adult cloned pigs and adult pigs from naturally bred control females using a series of physiological and genetic parameters, including detailed methylation profiles of selected genomic regions. Phenotypic and genetic analyses indicated that there are two classes of traits, one in which the cloned pigs have less variation than controls and another characterized by variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 20 publications
(25 reference statements)
6
51
1
Order By: Relevance
“…In fact, the expression of all but one gene (ARAF1) in organs of individual deceased clones was found to exceed this threshold and was likely abnormal (Table 2). Similar expression abnormalities were found in DNA methylation in cloned pigs and deceased cloned bovine calves (Archer et al 2003;Li et al, 2004;Yang et al, 2005). The same 2SD comparisons in the surviving clones revealed much less dysregulation (Table 2).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In fact, the expression of all but one gene (ARAF1) in organs of individual deceased clones was found to exceed this threshold and was likely abnormal (Table 2). Similar expression abnormalities were found in DNA methylation in cloned pigs and deceased cloned bovine calves (Archer et al 2003;Li et al, 2004;Yang et al, 2005). The same 2SD comparisons in the surviving clones revealed much less dysregulation (Table 2).…”
Section: Discussionsupporting
confidence: 62%
“…Faulty or incomplete epigenetic reprogramming has been observed in different stages of development (Cezar et al 2003;Kang et al 2001b;Mann et al 2003). Even in cloned animals that survive to term, different aspects of epigenetic abnormalities are evident, although the majority of these animals appear to be healthy and normal (Archer et al 2003;Li et al 2004;Xue et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The demethylation of these sequences was also shown to be similar to the in vivo produced blastocysts. Pre-1 and centromeric satellite sequences were found to have similar methylation levels in healthy cloned pigs and control pigs (Archer et al, 2003). However, even normal appearing pigs can have aberrant expression of imprinted genes (Jiang et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Although it is normally assumed that the use of cloned animals will exhibit less interindividual phenotypic variation and allow for a reduction of the number of animals needed to obtain statistically sound data, this assumption has been found not always to be warranted. For example, the variability in blood parameters and metabolites (Archer et al, 2003;Clausen et al, 2011) as well as the gene expression of fetal growth-related genes ( Jiang et al, 2007) was found to be similar in cloned as in normal pigs. It has been proposed that some of this variation may stem from maternal mitochondrial DNA from the donor cell (St. John et al, 2005).…”
Section: Introductionmentioning
confidence: 97%